STUDI PEMBUATAN MANISAN KERING KULIT BUAH SEMANGKA (Citrullus Lanatus) - Mhd.Iqbal Nusa; Misril Fuadi; Surya Sanjaya (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The objectives of this research was to study the effects of adding sugar concentrations and  the drying duration of  Water melon Fruit skin candy to quality aspects of  products. The study was conducted by using a Completed Randomized Design Factorial two factors and two reflications. The first factors were level  sugar concentration as G1=40%; G2=50%,G3=60%, and G4=70%. The second factors were the duration of drying as  L1= 10 hours, L2=12 hours, L3= 14 hours, and L4= 16 hours. The results showed that  the adding sugar concentrations caused  the different effect significantly to Total Soluble Solid (TSS), rendemen, moisture content, texture, and taste. The drying duration  caused  the different effect significantly to Total Soluble Solid (TSS), rendemen, moisture content, texture, and taste. Interaction effects of  factors did not cause the  different significantly to  the all parameters. The adding sugar concentrations  of 40%  and   drying duration  10 hours obtained the best quality of Water melon fruit skin candy.Keywords: sugar consentration, drying duration, quality of Water melon fruit skin candy